Crystal structures of pertussis toxin with NAD(+) and analogs provide structural insights into the mechanism of its cytosolic ADP-ribosylation activity - Sakari Moona; Tran Mai T; Rossjohn Jamie; Pulliainen Arto T; Beddoe Travis; Littler Dene R (ELSEVIER, 2022)
Bordetella pertussis is the causative agent of whooping cough, a highly contagious respiratory disease. Pertussis toxin (PT), a major virulence factor secreted by B. pertussis, is an AB5-type protein complex topologically related to cholera toxin. The PT protein complex is internalized by host cells and follows a retrograde trafficking route to the endoplasmic reticulum, where it subsequently dissociates. The released enzymatic S1 subunit is then translocated from the endoplasmic reticulum into the cytosol and subsequently ADP-ribosylates the inhibitory alpha-subunits (G alpha i) of heterotrimeric G proteins, thus promoting dysregulation of G protein-coupled receptor signaling. However, the mechanistic details of the ADP-ribosylation activity of PT are not well understood. Here, we describe crystal structures of the S1 subunit in complex with nicotinamide adenine dinucleotide (NAD+), with NAD+ hydrolysis products ADP-ribose and nicotinamide, with NAD+ analog PJ34, and with a novel NAD+ analog formed upon S1 subunit crystallization with 3-amino benzamide and NAD+, which we name benzamide amino adenine dinucleotide. These crystal structures provide unprecedented insights into pre-and post-NAD+ hydrolysis steps of the ADP-ribosyltransferase activity of PT. We propose that these data may aid in rational drug design approaches and further development of PT-specific small-molecule inhibitors.